Relationship of CD146 expression to secretion of interleukin (IL)‐17, IL‐22 and interferon‐γ by CD4+ T cells in patients with inflammatory arthritis. (March 2015) - Wu, C.; Goodall, J. C.; Busch, R.; Gaston, J. S. H.
Summary Expression of the adhesion molecule, CD146/MCAM/MelCAM, on T cells has been associated with recent activation, memory subsets and T helper type 17 (Th17) effector function, and is elevated in inflammatory arthritis. Th17 cells have been implicated in the pathogenesis of rheumatoid arthritis (RA) and spondyloarthritides (SpA). Here, we compared the expression of CD146 on CD4+ T cells between healthy donors (HD) and patients with RA and SpA [ankylosing spondylitis (AS) or psoriatic arthritis (PsA)] and examined correlations with surface markers and cytokine secretion. Peripheral blood mononuclear cells (PBMC) were obtained from patients and controls, and synovial fluid mononuclear cells (SFMC) from patients. Cytokine production [elicited by phorbol myristate acetate (PMA)/ionomycin] and surface phenotypes were evaluated by flow cytometry. CD146+CD4+ and interleukin (IL)‐17+CD4+ T cell frequencies were increased in PBMC of PsA patients, compared with HD, and in SFMC compared with PBMC. CD146+CD4+ T cells were enriched for secretion of IL‐17 [alone or with IL‐22 or interferon (IFN)‐γ] and for some putative Th17‐associated surface markers (CD161 and CCR6), but not others (CD26 and IL‐23 receptor). CD4+ T cells producing IL‐22 or IFN‐γ without IL‐17 were also present in the CD146+ subset, although their enrichment was less marked. Moreover, a majority of cells secreting these cytokines lacked CD146. Thus, CD146 is not a sensitive or specific marker of Th17 cells, but rather correlates with heterogeneous cytokine secretion by subsets of CD4+ helper T cells.